Accidents at work with sharps in the surgical center unit in southern Brazil - Ottobelli, Caroline; Cezar-Vaz, Marta Regina; dos Santos Cargnin, Marcia Casaril; Argenta, Carla; Zanatta, Rosa Gabriela (O Mundo da Saúde, 2015)
The study aimed to identify occupational accidents in a surgical center unit in a general hospital in the northern area in the state of Rio Grande do Sul. Quantitative study, descriptive and documentary type, in which notifications of occupational accidents occurred between 2001 and 2012 were analyzed. Data collection occurred through the notifications of occupa- tional accidents, totaling 64 records. Occupational accidents occurred with women (n=59; 92%), exercising the profession of nursing (n=61; 95%), active in the profession at an average of three years. Most accidents occurred during the morning and afternoon, with needlestick, and hands were the most affected area. It was concluded that actions should be proposed to the most affected subjects, so that the number of accidents decrease.